Landscape Photography: Tropical Scenes. - Reznick, Justin (linkedin.com, 2017)
Learn how to photograph the essence of tropical landscapes, foliage, and other nature scenes. Discover how to choose and protect equipment, photograph sunsets, trees, and more.